2021
DOI: 10.1177/1756286421997372
|View full text |Cite
|
Sign up to set email alerts
|

Teriflunomide treatment is associated with optic nerve recovery in early multiple sclerosis

Abstract: Background and aims: Various attempts have been made to support recovery following optic neuritis (ON), but the respective trials have mostly been negative. The aim of this study was to determine whether disease-modifying treatment (DMT) following ON as first manifestation of relapsing-remitting multiple sclerosis influences long-term outcomes. Methods: A total of 79 patients with ON were identified and evaluated at relapse, DMT induction, and 12 months following treatment induction with either glatiramer acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, a previous study revealed teriflunomide to impair microglial activation in a mutant PLP mouse model [ 26 ], indicating that also resident immune cells are tamed further contributing to an overall beneficial effect. Accordingly, a recent clinical study indicated that teriflunomide treatment is associated with favorable outcomes regarding functional optic nerve recovery following optic neuritis in early multiple sclerosis [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study revealed teriflunomide to impair microglial activation in a mutant PLP mouse model [ 26 ], indicating that also resident immune cells are tamed further contributing to an overall beneficial effect. Accordingly, a recent clinical study indicated that teriflunomide treatment is associated with favorable outcomes regarding functional optic nerve recovery following optic neuritis in early multiple sclerosis [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…iii) Secondary progressive MS (SPMS): This type follows RRMS, but with more severe symptoms. iv) Progressive relapsing MS (PRMS): In this type, symptoms worsen from the beginning with periods of remission ( 4 , 5 ).…”
Section: Categories Of Multiple Sclerosismentioning
confidence: 99%